Predictive analysis of cognitive skills achievements in mathematics along seven logical operations among elementary pre-service teachers - Baking, Rainnier Duran; Ibarra, Florante Pasardan; Mukminin, Amirul (Edelweiss Applied Science and Technology, 2023)
The study aimed to examine the predictors of cognitive skill achievement along seven logical operations in mathematics based on academic aspects and social learning domains among 328 elementary preservice teachers at Central Luzon State University during the second semester. This study utilized a quantitative method with descriptive and correlational approaches. A total of 328 pre service elementary teachers at Central Luzon State University participated in a study that aimed to assess their academic elements, social learning domains, and cognitive skills achievements. To collect the data, a standardized research instrument taken from the National Assessment of Educational Progress (NAEP) based on the Scenario-Based Task (SBT) was adapted to measure academic and social learning domains, while the Test on Logical Operations (TLO) was used to determine their cognitive skills achievement in mathematics along seven logical operations (classification, seriation, logical multiplication, compensation, ratio and proportional thinking, probability thinking, and correlational thinking). The results revealed that year level, preferred subject to teach, cognitive aspects, affective domain, and cognitive development practice as components of the social learning domain were found to influence cognitive skills achievement in mathematics. Further assessment is recommended on two distinct variables to find the connection between cognitive skills achievement applicable to elementary preservice teachers and metacognitive skills achievement for secondary prospective teachers. Cognitive development practice shows that one is capable of using the brain to comprehend various numerical concept processes, and it is more prospective to affect his or her capability to adjust to a particular environmental condition for learning the logic operations of numeracy.